Effect of Manual Therapy in Reducing Neck Pain in Patients with Hernia Nucleus Polposus Cervicalis - Putro, Dimas Liwung Sasongko; Sudaryanto, Wahyu Tri (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Herniated Nucleus Pulposus Cervicalis (HNPC) is a medical condition characterized by the posterior or posterolateral protrusion of the intervertebral disc, resulting from the degeneration of the fibrous annulus. This protrusion exerts pressure on the nerve roots and spinal cord, leading to the development of neurological disorders. The objective of this study was to assess the efficacy of manual therapy in alleviating neck pain among patients diagnosed with cervical herniated nucleus pulposus. Subjects and Method: A randomized controlled trial was carried out at JIH Hospital in Yogyakarta from August to September 2023. Fourteen patients diagnosed with cervical herniated nucleus pulposus (HNPC) were purposively sampled for the study. Seven patients underwent manual therapy as an intervention, while the remaining seven received standard treatment as the control group. The dependent variable assessed was neck pain, measured using a visual analogue scale (VAS). The independent variable was orthopedic manual physical therapy. The differences in neck pain scores between the two groups were analyzed using an independent t-test. Results: Following the intervention, the pain score in the intervention group (Mean 2.43; SD= 1.13) exhibited a significant reduction compared to the control group (Mean= 4.86; SD= 0.90), with a p-value of 0.001. Conclusion: Orthopedic manual therapy effectively alleviates neck pain in individuals with cervical herniated nucleus pulposus.